Effect of Turmeric Juice Drink on Blood Pressure Reduction in Elderly Hypertensive Patients in East Pentadio Village, Telaga Biru District - Taufik A. Mustafa; Hamna Vonny Lasanuddin; Rosmin Ilham (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Hypertension is a health problem that often occurs in the elderly and is at risk of causing various complications if not controlled properly. In addition to pharmacological therapy, non-pharmacological interventions that are safe and easy to apply are needed, one of which is through the use of herbal ingredients. This study aims to determine the effect of giving turmeric juice drink on reducing blood pressure in elderly people with hypertension in East Pentadio Village, Telaga Biru District. This study uses a pre-experimental design with a one group pretest–posttest approach. The study sample was elderly people with hypertension who were selected by total sampling technique. The intervention was in the form of giving 150 ml of turmeric juice drink once a day for seven days. Systolic and diastolic blood pressure measurements were carried out before and after the intervention, then analyzed using the Wilcoxon test. The results showed a decrease in the mean systolic and diastolic blood pressure after the administration of turmeric juice drink, with a p value of < 0.05 which showed a significant effect. It can be concluded that turmeric juice drink has an effect on reducing blood pressure in the elderly with hypertension and can be used as an alternative non-pharmacological therapy in controlling hypertension in the elderly.